NILAI DALAM GEGURITAN CUPAK - Maryani, Pande Putu Yayuk (Humanis, 2013)
This research is explaining about traditional Balinese literature of  geguritan with the theme “Geguritan Cupak ”. In this geguritan there are seven kinds of pupuh in 429 verses. The purpose of this research is to acknowledge the essence value in the geguritan. This research has two goals which is general purpose and special purpose. The general purpose of this research is to support the development of literature, and also to give information or as a tool for the importancy of assistance and development of society culture about the existence of the literature in geguritan. Another general purpose is the spread out yhe result of the geguritan literature research especially Geguritan Cupak. The special purpose of this research is to describe the contained value within Geguritan Cupak. The method used in data supply phased is reading method, in data analysis phase is qualitative method, and the phase of data analysis result is the formal and informal method. To support these methods, the technical of notes is used. The result that gained in this research, is the values that the outhor wants to say which are religion value, heroic value, and loyalty.
Keywords: Geguritan, value, and Cupak.